Chemokine Receptor 2 (CXCR2) Gene Variants and Their Association with Periodontal Bacteria in Patients with Chronic Periodontitis - Denisa Kavrikova; Petra Borilova Linhartova; Svetlana Lucanova; Hana Poskerova; Antonin Fassmann; Lydie Izakovicova Holla (Mediators of Inflammation)
Periodontitis, an inflammatory disease caused by subgingival Gram-negative (G-) bacteria, is linked with loss of the connective tissue and destruction of the alveolar bone. In the regulation of inflammatory response, chemokine receptor 2 (CXCR2), a specific receptor for interleukin-8 and neutrophil chemoattractant, plays an important role. The first aim of this study was to investigate the CXCR2 gene variability in chronic periodontitis (CP) patients and healthy nonperiodontitis controls in the Czech population. The second aim was to find a relation between CXCR2 gene variants and the presence of periodontal bacteria. A total of 500 unrelated subjects participated in this case-control study. 329 CP patients and 171 healthy nonperiodontitis controls were analyzed using polymerase chain reaction techniques for three single-nucleotide polymorphisms (SNPs): +785C/T (rs2230054), +1208T/C (rs1126579), and +1440A/G (rs1126580). A DNA microarray detection kit was used for the investigation of the subgingival bacterial colonization, in a subgroup of CP subjects (N=162). No significant differences in allele, genotype, haplotype, or haplogenotype frequencies of CXCR2 gene variants between patients with CP and healthy controls (P>0.05) were determined. Nevertheless, Aggregatibacter actinomycetemcomitans was detected more frequently in men positive for the C allele of the CXCR2 +785C/T polymorphism (61.8% vs. 41.1%, P<0.05; OR=2.31, 95% CI=1.03-5.20) and for the T allele of the CXCR2 +1208C/T variant (61.8% vs. 38.9%, P<0.05; OR=2.54, 95% CI=1.13-5.71). In contrast, no statistically significant associations of CXCR2 variants with seven selected periodontal bacteria were found in women. Although none of the investigated SNPs in the CXCR2 gene was associated with CP, the CXCR2 gene variants can be associated with subgingival colonization of G- bacteria in men with CP in the Czech population.